Experimental study of the pattern infection with cutaneous leishmaniasis between males and females of mice - Mahdi Jarallah, Hind (University of Thi-Qar Journal of Science, 2011)
In the present study the development of skin lesions in males and females BALB/c miceinfected with Leishmania major strain was investigated. The results of this study demonstrated that the infection with cutaneous leishmaniasis begins in females before males and there are differences in appearance and development of skin ulcers was found between males and females of mice throughout the experiment (6 months). The heavily infected parts were completely lost from the mice body. The metastatic cutaneous lesions were observed on both sex males and females.